Evaluation of Different Steel Wastes and its Influence in Ceramic Bricks Shaping by Extrusion. (2015) - Quaranta, Nancy; Pelozo, Gisela; Díaz, Osmell
Abstract: Steel companies generate large amounts of wastes, which usually are deposited within them, reducing the available place. Because of this, there have been numerous studies to reduce the generation of residues and reuse them transforming into byproducts from other industries. In this paper the influence of using different feedstock steel discards added to clays to obtain construction ceramics was investigated. The studied wastes are: steel slag, white powders, blast furnace sludge and post-mortem aluminosilicate refractories. For the analysis of discards and clay various characterization techniques were used, such as optical microscopy and scanning electron microscopy, energy dispersive analysis of X-ray, X-ray diffraction analysis, particle size distribution. Mixtures with additions up to 50% residue and the clay commonly used in forming ceramic tiles were analyzed by the method of Casagrande apparatus (ASTM D4318) to obtain the fluid and plastic limits, and the plasticity index of each. According to the analysis, it can be established that the plasticity of the mixtures is greatly influenced by the wastes addition, being the steel slag and post-mortem aluminosilicate refractories, those which most lowered the index, affecting negatively the extrusion forming of the products.